Frobenius Splitting Methods in Geometry and Representation Theory - Brion, Michel; Kumar, Shrawan; SpringerLink (Online service) (Boston, MA : Birkhäuser Boston, 2005)
The theory of Frobenius splittings has made a significant impact in the study of the geometry of flag varieties and representation theory. This work, unique in book literature, systematically develops the theory and covers all its major developments. Key features: * Concise, efficient exposition unfolds from basic introductory material on Frobenius splittings definitions, properties and examples to cutting edge research * Studies in detail the geometry of Schubert varieties, their syzygies, equivariant embeddings of reductive groups, Hilbert Schemes, canonical splittings, good filtrations, among other topics * Applies Frobenius splitting methods to algebraic geometry and various problems in representation theory * Many examples, exercises, and open problems suggested throughout * Comprehensive bibliography and index This book will be an excellent resource for mathematicians and graduate students in algebraic geometry and representation theory of algebraic groups.
Frobenius Splitting: General Theory -- Frobenius Splitting of Schubert Varieties -- Cohomology and Geometry of Schubert Varieties -- Canonical Splitting and Good Filtration -- Cotangent Bundles of Flag Varieties -- Equivariant Embeddings of Reductive Groups -- Hilbert Schemes of Points on Surfaces.
Keywords: Mathematics; Algebraic geometry; Group theory; Mathematics; Algebraic Geometry; Group Theory and Generalizations; Electronic books